2017
DOI: 10.1016/j.athoracsur.2016.05.089
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Performance of a Sutureless Bioprosthesis With Two Pericardial Stented Valves on Small Annuli: An In Vitro Study

Abstract: All of the valves tested provided good fluid dynamic performances. The sutureless bioprosthesis provided the best performance with the least hindrance to flow behavior. From the hydrodynamic perspective, the sutureless prosthesis may present an advance in the evolution of bioprostheses, ensuring low gradients and potential for low incidence of patient-prosthesis mismatch even in small annuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…In vitro studies demonstrated superiority of RPD compared with conventional bioprostheses (Crown PRT, Edwards Perimount Magna, and Magna Ease) in terms of hemodynamic performance. 8,9 In this real-world experience, larger prosthesis size did not translate into improved mean gradients at rest. Nevertheless, elderly patients with small aortic annuli could benefit from the use of RPD through faster implantation and less need for aortic root enlargement.…”
Section: Prosthesis Size and Hemodynamic Outcomesmentioning
confidence: 67%
See 1 more Smart Citation
“…In vitro studies demonstrated superiority of RPD compared with conventional bioprostheses (Crown PRT, Edwards Perimount Magna, and Magna Ease) in terms of hemodynamic performance. 8,9 In this real-world experience, larger prosthesis size did not translate into improved mean gradients at rest. Nevertheless, elderly patients with small aortic annuli could benefit from the use of RPD through faster implantation and less need for aortic root enlargement.…”
Section: Prosthesis Size and Hemodynamic Outcomesmentioning
confidence: 67%
“…7 RPD are supposedly hemodynamically advantageous due to the absence of a suture ring with larger effective orifice areas, resulting in lower pressure gradients in vitro. 8,9 This theoretical advantage has not been investigated in clinical real-world studies so far. In this retrospective propensity score matched single-center study, we compare hemodynamic outcome of RPD with conventional aortic bioprostheses.…”
Section: Introductionmentioning
confidence: 99%
“…However, we recorded a mean transvalvular gradient of 12.6 ± 4.2 mm Hg at rest, with an EOA of 1.5 ± 0.5 cm 2 . Interestingly, Tasca et al . demonstrated that small size sutureless valve provided lowest gradients and larger EOA in an in vitro study, compared to two standard pericardial stented bioprostheses.…”
Section: Discussionmentioning
confidence: 99%
“…Tasca et al29 demonstrated that small size sutureless valve provided lowest gradients and larger EOA in an in vitro study, compared to two standard pericardial stented bioprostheses. These results have been confirmed clinically by Shresta et al,20 who observed a mean gradient of 13.6 ± 5.4 cm 2 and an EOA of 1.5 ± 0.25 cm 2 in a cohort of elderly patients with preoperative annulus ≤22 mm.…”
mentioning
confidence: 99%
“…These prostheses are intended to combine the advantages of conventional surgery-the controlled, complete removal of the degenerated native valve, the safety and the control of possible complications, and the long durability of the prostheses made from bovine pericardium-and of transcatheter techniques (fast implantation, less invasive access). Hemodynamics are generally rated better thanks to the smaller stent frame (24). Rapid deployment prostheses were initially recommended as therapeutic alternatives to conventional bioprostheses (25).…”
Section: Advantages and Disadvantagesmentioning
confidence: 99%